PEMBERDAYAAN MASYARAKAT MELALUI BIMBINGAN PELATIHAN MEMBATIK DI PKBM MARSUDI KARYA BIDANG PENGEMBANGAN KEWIRAUSAHAAN [COMMUNITY EMPOWERMENT THROUGH BATIK TRAINING GUIDANCE AT PKBM MARSUDI KARYA FOR ENTREPRENEURSHIP DEVELOPMENT] - Suryatini, Lilis; Wiyani, Novan Ardy (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2023)
Community empowerment is one of the studies of non-formal education because it includes adult education practices such as training. Community empowerment can be used as a solution to eradicate unemployment. This has been implemented by many government and private programs. Empowerment, if seen as a process, is a stage of activity to strengthen community power which is still considered weak, whereas if seen from its objectives, empowerment is an activity to achieve a goal which includes social change and community independence. The method used is qualitative with a descriptive approach. Community empowerment through Banyumasan Batik production is implemented through stages in accordance with several existing theories. The conclusion of this research shows that implementing empowerment through the correct stages of empowerment will make it easier to achieve empowerment goals as planned so that empowerment can also be achieved from a socio-economic, political and psychological perspective. The existence of good cooperation between facilitators and beneficiaries will achieve empowerment goals easily, this can be used as advice for problems that exist in the empowerment process through the production of Banyumasan Batik in Patikraja Village.